(untitled) (Vietnam Journal of Community Medicine, 2024)
Objective: Describe the clinical and subclinical characteristics of patients with neurological bladder due to spinal cord injury at the Rehabilitation Center, Bach Mai Hospital in 2022 Subject and method: The cross-sectional description at 2 points (week 1, week 4) of patients was performed on 133 patients aged 18 years and older, diagnosed with neurocystal bladder treatment at the Rehabilitation Center, Bach Mai Hospital. Analyze the data on SPSS 16.0 with a table describing the frequency and ratio. Results: The ratio of men /women was 2/1, the average age was 47.58 years (6-87), 34.6% of patients diagnosed pulpitis before hospitalization; 87.3% of patients had paralysis of the lower limbs; 15.8% of patients had urinary infections, accounting for a high proportion of K.Pneumoniae bacteria 12%. The patient’s hematological and biochemical indices fluctuate little during the treatment process. Conclusion: Spinal cord injuries with nerve bladder are mainly seen in middle-aged men, accounting for the majority of patients with paralysis of the lower two limbs, the urinary infection is still high and the bacterial infection accounts for a high proportion of K.pneumoniae bacteria. The patient’s hematological and biochemical indices fluctuate little during the treatment process.